2007
DOI: 10.1089/ten.2006.0013
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Stromal Cell–Derived Factor-1alphaIn SituIncreases C-kit+Cell Homing to the Infarcted Heart

Abstract: Stromal-derived factor 1alpha (SDF-1alpha) is a key stem cell homing factor that is crucial for mobilization of stem cells from bone marrow to peripheral blood and subsequent engraftment to the tissue of diseased organs. It has been reported that SDF-1alpha is transiently over-expressed in ischemic myocardium. Therefore, there may be a limited time window after acute myocardial infarction (AMI) during which stem cells are recruited to injured myocardium for repair. This study aimed at investigating whether con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 31 publications
2
123
0
4
Order By: Relevance
“…For example, SDF-1 expression is expressed by the injured myocardium less than 1 week after myocardial infarction 5 and MCP-3 for less than 10 days. 14 Multiple studies have demonstrated that the delivery of SDF-1 to the myocardium either through cell-based gene therapy, 5,12,32,49 gene trans- fer, 50 or protein 51,52 leading to prolongation, or reestablishment of SDF-1 expression at times late after myocardial infarction leads to stem cell homing, an increase in vascular density, 5,32,49,53 activation and homing of cardiac stem cells, 55 and improvement in cardiac function. Furthermore, engineering of MSCs or HSCs to overexpress SDF-1 receptor CXCR4 similarly leads to greater homing of engineered MSCs and improved left ventricular function compared to control MSCs or HSCs when the cells were delivered within 24 hours of myocardial infarction.…”
Section: Stem Cell Homingmentioning
confidence: 99%
“…For example, SDF-1 expression is expressed by the injured myocardium less than 1 week after myocardial infarction 5 and MCP-3 for less than 10 days. 14 Multiple studies have demonstrated that the delivery of SDF-1 to the myocardium either through cell-based gene therapy, 5,12,32,49 gene trans- fer, 50 or protein 51,52 leading to prolongation, or reestablishment of SDF-1 expression at times late after myocardial infarction leads to stem cell homing, an increase in vascular density, 5,32,49,53 activation and homing of cardiac stem cells, 55 and improvement in cardiac function. Furthermore, engineering of MSCs or HSCs to overexpress SDF-1 receptor CXCR4 similarly leads to greater homing of engineered MSCs and improved left ventricular function compared to control MSCs or HSCs when the cells were delivered within 24 hours of myocardial infarction.…”
Section: Stem Cell Homingmentioning
confidence: 99%
“…Controversial results have been reported on the expression of these genes in similar studies. CXCL12 is considered to play and important role in the recovery of MI (26)(27)(28)(29)(30)(31), but its expression in the infarcted heart or in the plasma is not always high. In rats, CXCL12 was detected 1 day after infarction, peaking on day 7 and declining to basal levels around 14 days later (32).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, plasma levels of CXCL12 gradually decreased between 2, 7 and 60 days after MI (22). Although controversial, these studies do not alter the role that CXCL12 plays in the recovery of MI (26)(27)(28)(29)(30)(31). In a recent study, it was observed that the overexpression of CXCR4 (SDF-1 receptor) enhanced MSC recruitment and penetration into the ischemic regenerative niche, resulting in more efficient tissue repair (33).…”
Section: Discussionmentioning
confidence: 99%
“…Positive results were reported by Zhang G. et al, who reported that PEGylated fibrin NFs loaded with SDF-1 (100 ng), when injected in a mouse MI model, significantly increased myocardial recruitment of c-kit + cells compared to controls two weeks after treatment. Enhanced stem cell homing was maintained at 28 days, when LV function was significantly improved in comparison with the controls [100]. More recently, our group prepared smooth polymeric NFs of stat-modified PLGA to deliver NRG to the heart.…”
Section: Nanofibers In Protein-based Therapiesmentioning
confidence: 96%